Juridical Review Regarding The Division Of Inheritance To Only Children Who Have Adopted Brothers In The Perspective Of Islamic Law - Novitasari, Ika; Amaliah, Rezki (Kirana Publisher (KNPub), 2023)
The problem in this paper is a Juridical Review Regarding the Distribution of Inheritance to an Only Child who has an Adopted Sibling in the perspective of Islamic law. This type of research is classified as normative research using the principles and problems studied. Research results show that 1. The main factor causing the adopted child not to obtain inheritance rights is because they do not have blood relations or in another sense, there are family members of the adoptive parents who are more close or blood related than the child, 2. An only child who has an adopted sibling still gets Inheritance according to what is specified in the Qur'an, and adopted children in Islamic inheritance law are not allowed to inherit property from their adoptive parents but are encouraged to provide grants or wills for the welfare of their adopted children. The granting or will is as much as 1/3 part as a mandatory will, based on article 209 paragraph (2) of the Compilation of Islamic Law. Adopted children are not included in the 2 categories mentioned above, because adopted children are not the same relative or descendant of their adoptive parents, therefore, between adopted children and their adoptive parents are not entitled to inherit from each other.